2001
DOI: 10.1073/pnas.201399298
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the nonmevalonate pathway to terpenes: The role of the GcpE (IspG) protein

Abstract: Recombinant Escherichia coli cells engineered for the expression of the xylB gene in conjunction with genes of the nonmevalonate pathway were supplied with 13 C-labeled 1-deoxy-D-xylulose. Cell extracts were analyzed directly by NMR spectroscopy. 13 C-labeled 2C-methyl-D-erythritol 2,4-cyclodiphosphate was detected at high levels in cells expressing xylB, ispC, ispD, ispE, and ispF. The additional expression of the gcpE gene afforded 1-hydroxy-2-methyl-2-(E)-butenyl 4-diphosphate as an intermediate of the nonm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
157
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(167 citation statements)
references
References 31 publications
8
157
1
1
Order By: Relevance
“…Based on the similarity of the EPR signals in GcpE and FTR we propose that the transient signal detected in GcpE is due to binding and stabilization of a radical-type intermediate by the 4Fe cluster. This is an important finding since several mechanisms have been proposed in the literature [10,13,16,33], but in only two papers was a direct role proposed for the 4Fe cluster [11,34].…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on the similarity of the EPR signals in GcpE and FTR we propose that the transient signal detected in GcpE is due to binding and stabilization of a radical-type intermediate by the 4Fe cluster. This is an important finding since several mechanisms have been proposed in the literature [10,13,16,33], but in only two papers was a direct role proposed for the 4Fe cluster [11,34].…”
Section: Resultsmentioning
confidence: 91%
“…This procedure, however, can result in the presence of a mix of clusters types. Sequence alignments of the available GcpE sequences [13][14][15][16][17] show that there are only three highly conserved cysteine residues that in principle can coordinate a [4Fe-4S] cluster that contains a unique Fe atom or a [3Fe-4S] cluster. In the case of enzyme from Thermosynechococcus elongatus the reconstitution procedure resulted in an enzyme preparation that showed an absorption spectrum with bands at 305, 395 and 585 nm, which was interpreted as being due to a [4Fe-4S] + cluster [12].…”
Section: Introductionmentioning
confidence: 99%
“…Then, DXP is transformed to MEP, catalyzed by DXR [14]. Finally, MEP is converted to IPP and DMAPP after consecutive steps catalyzed by 2-C-methyl-d-erythritol-4-phosphate cytidylyltransferase (CMS), 4-(cytidine 5′-diphospho)-2-C-methyl-d-erythritol kinase (CMK), 2-C-methyl-derythritol-2,4-cyclodiphosphate synthase (MCS), 4-hydroxy-3-methylbut-2-enyl diphosphate synthase (HDS), 4-hydroxy-3-methylbut-2-enyl diphosphate reductase (HDR) and isopentenyl diphosphate isomerase (IPI) [9,5,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of tZR 5Ј-monophosphate (tZRMP) from AMP and 4-hydroxy-3-methyl-2-(E)-butenyl diphosphate (HMBDP), a likely precursor, has been demonstrated to be catalyzed by TZS, an agrobacterial IPT (14). However, HMBDP was identified as a metabolic intermediate of the methylerythritol phosphate (MEP) pathway (15), which occurs in bacteria and plastids (16). Selective labeling experiments using 13 Clabeled precursors specific for either the MEP or MVA pathway demonstrated that the isoprenoid side chain of iP and tZ predominantly originates from the MEP pathway, whereas a large fraction of the cZ side chain is derived from the MVA pathway (17).…”
mentioning
confidence: 99%